UJI EFIKASI FORMULASI RODENTISIDA CAIR DENGAN BAHAN AKTIF PERMENTRIN DAN MALATHION PADA TIKUS SAWAH, TIKUS RUMAH DAN TIKUS POHON DALAM MENCEGAH PENYAKIT LEPTOSPIROSIS - Supriyo, Edy; Pujihastuti, Isti; Broto, RTD Wisnu; Arifan, Fahmi (Gema Teknologi, 2020)
Mice are the main reservoir in transmitting leptospirosis, which is an infectious zoonotic disease caused by pathogenic leptospira bacteria, so it needs to be controlled effectively. Mice control has been using traps or rodenticides. One of the pesticides available is permethrin and malathion, which has been used as an insecticide. The purpose of this study was to determine the effectiveness of insecticide formulas as rodenticides in killing field mice, house mice, and tree mice. In the research of liquid rodenticide formula, the concentration is 0.025; 0.050 and 0.075% of the active ingredients were tested for efficacy against mice. Data analysis in the form of descriptive. The results showed that the absence of mice that died from these three types of mice, which showed a dose of 0.075%, was too small for mice so that they only experienced seizures. So that further testing is needed to make the killing power more effective on mice.